Social Work Penalties For Perpetrators Of Minor Crimes In The Development Of Indonesian Criminal Law - Nani Widya Sari; Guntarto Widodo; Oksidelfa Yanto; Fariz Rifqi Hasbi; Rifka Zuwanda (CV. Tirta Pustaka Press, 2026)
This study examines the legal regulation and implementation of community service punishment for minor offenses within the framework of Indonesian criminal law reform, as well as their application to minor offenders. The method used is normative juridical research, which emphasizes the study of rules and legislation related to community service penalties. The study reveals that the enactment of Law Number 1 of 2023 introduces community service punishment as an alternative sanction for minor offenses, reflecting a shift from imprisonment-oriented sentencing toward rehabilitative and restorative justice policies. The analysis demonstrates that community service punishment constitutes a more proportional and rehabilitative sanction for minor crimes compared to short-term imprisonment or monetary fines, aiming to improve offender behavior and restore social relationships. Effective implementation requires institutional readiness, inter-agency coordination among law enforcement bodies, and adequate supervisory mechanisms within the criminal justice system to ensure community service effectively functions as a substitute for imprisonment.